Incidence, Predictors, and Outcomes Associated With Hypotensive Episodes Among Heart Failure Patients Receiving Sacubitril/Valsartan or Enalapril: The PARADIGM-HF Trial (Prospective Comparison of Angiotensin Receptor Neprilysin Inhibitor With Angiotensin-Converting Enzyme Inhibitor to Determine Impact on Global Mortality and Morbidity in Heart Failure). (April 2018) - Vardeny, Orly; Claggett, Brian; Kachadourian, Jessica; Pearson, Scott M.; Desai, Akshay S.; Packer, Milton; Rouleau, Jean; Zile, Michael R.; Swedberg, Karl; Lefkowitz, Martin; Shi, Victor; McMurray, John J.V.; et al.
Abstract : Background: In PARADIGM-HF (Prospective Comparison of Angiotensin Receptor Neprilysin Inhibitor With Angiotensin-Converting Enzyme Inhibitor to Determine Impact on Global Mortality and Morbidity in Heart Failure), heart failure treatment with sacubitril/valsartan reduced the primary composite outcome of cardiovascular death or heart failure hospitalization compared with enalapril but resulted in more symptomatic hypotension. Concern on hypotension may be limiting use of sacubitril/valsartan in appropriate patients. Methods and Results: We characterized patients in PARADIGM-HF by whether they reported hypotension during study run-in periods (enalapril, followed by sacubitril/valsartan) and after randomization and assessed whether hypotension modified the efficacy of sacubitril/valsartan. Of the 10 513 patients entering the enalapril run-in, 136 (1.3%) experienced hypotension and 93 (68%) were unable to continue to the next phase; of 9419 patients entering the sacubitril/valsartan run-in period, 228 (2.4%) patients experienced hypotension and 51% were unable to successfully complete the run-in. After randomization, 388 (9.2%) participants had 501 hypotensive events with enalapril, and 588 (14.0%) participants had 803 hypotensive events with sacubitril/valsartan ( P <0.001). There was no difference between randomized treatment groups in the number of participants who discontinued therapy because of hypotension. Individuals with a hypotensive event in either group were older, had lower blood pressure at randomization, and were more likely to have an implantable cardioverter defibrillator. Participants with hypotensive events during run-in who were ultimately randomized derived similar efficacy from sacubitril/valsartan compared with enalapril as those without hypotensive events ( P interaction>0.90). Conclusions: Hypotension was more common with sacubitril/valsartan relative to enalapril in PARADIGM-HF but did not differentially affect permanent discontinuations. Patients with hypotension during run-in derived similar benefit from sacubitril/valsartan compared with enalapril as those who did not experience hypotension.